Sexual harassment of working women from legalization to criminalization : the silent crime - Bouzennoune, Saida (Journal of Human Sciences, 2022)
Sexual harassment of working women is one of the dangerous phenomena that threaten the Algerian society in its values ​​and morals, as it appeared from the manifestations of the abuse of power at work as physical violence practiced on women. Even children alike is what necessitated legislative intervention by criminalizing the act with the text of Article 341 bis first, then the text of Article 333 bis of the Penal Code and other articles that prohibit verbal and physical harassment at work.